PROGRESSIVE WEB APP-BASED ONLINE REPAIR SHOP APPLICATION USING MAPBOX AND GEOLOCATION API - Putra Rahmat, Muhammad Aryo; Nofiyati, Nofiyati; Permadi, Ipung (Informatika, Universitas Jenderal Soedirman, 2023)
Motorcycle users in Indonesia continue to increase every year. This has implications for the increasing need for motorcycle repair or maintenance service providers. This need is an emergency, but this is a problem because the lack of information regarding the location of the nearest workshop makes the process of finding a repair shop consuming a lot of time and energy. This study aims to develop an Online Workshop application that can present a map with the nearest repair shop location using Mapbox and the Geolocation API to make it easier for motorbike users to find a repair shop. In addition, this application allows users to be able to call a mechanic to come to the location. The Bengkel Online application is built using Firebase as a database and applies progressive web apps technology. The results of this study indicate that the online workshop application can be used to order repair services and call a mechanic to the location properly and accurately as indicated by the results of application testing which shows that all features function properly.